2016
DOI: 10.1063/1.4953605
|View full text |Cite
|
Sign up to set email alerts
|

Control of sawtooth via ECRH on EAST tokamak

Abstract: Localized electron heating produced by electron cyclotron resonant heating (ECRH) system has been proven to be powerful tools for controlling sawtooth instabilities, because such system allows to directly modify the local plasma parameters that determine the evolution of sawtooth periods. In this paper, we present the experimental results carried out on experimental advanced superconducting tokamak (EAST) with regard to sawtooth period control via ECRH. The electron cyclotron heating system on EAST was capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…However, the counter-ECCD seems to have few effects on the mode stabilization. The sawtooth period is found to be minimized in EAST experiments [14] when the ECRH resonance location is deposited to be just inside the q =1 surface, as shown in the Fig. 11(b).…”
Section: Preliminary Results From Ecrhmentioning
confidence: 96%
“…However, the counter-ECCD seems to have few effects on the mode stabilization. The sawtooth period is found to be minimized in EAST experiments [14] when the ECRH resonance location is deposited to be just inside the q =1 surface, as shown in the Fig. 11(b).…”
Section: Preliminary Results From Ecrhmentioning
confidence: 96%
“…Till now, the launcher is stably operated under 100 s pulse length with 500kW injection power. The influence on sawtooth period and tearing mode stabilizing were investigated due to the flexible steering capability [21].…”
Section: Engineering Commissioningmentioning
confidence: 99%
“…[15][16][17] Furthermore, in EAST, it is observed that the combined heating of LHW and ECRH can alleviate and avoid the effect of the sawtooth oscillation on the impurity transport. [18][19][20] The results regarding this combined heating for improving the core impurity confinement will be beneficial to the EAST long-pulse steady-state and high-performance operation with tungsten divertor.…”
Section: Introductionmentioning
confidence: 99%